THE IMPORTANCE OF THE ARTISAN WINE AGROINDUSTRY - Luquesi, Cristiane Monique Sanches; Ferrarezi Junior, Edemar (Revista Interface Tecnológica, 2022)
The Brazilian wine production sector is composed mainly, and in large part, of small rural and family producers. Despite the limitations that still exist in the Brazilian artisanal viticulture scenario, the production and final result of artisanal wines grow in consumer taste. The market and consumption of wine has been growing significantly in Brazil, per capita consumption corresponded to 1.72 liters, a very significant result. The present work was carried out through the method of bibliographic review of scientific articles, books, magazines and electronic sites that are related to the theme, as well as the search for information and news about family agro-industries of artisanal wine, and demonstrates that the construction of a Vineyard of artisanal wines is a great income enterprise for rural producers and their families, with the objective of bringing to light guidelines for the construction of a viticulture of artisanal origins, proving to be a type of growing business in the market.
Keywords: Agroindustry; Wine; Viticulture; Artisanal wine